The Impact of Economic Inequality on Social Disparities: A Quantitative Analysis - Humala Simangunsong; Baldry Pitre Stewart; Debortoli Debortoli (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2023)
This quantitative study examines the complex relationship between economic inequality and social inequities, focusing on educational attainment. The study examines how Gini coefficient-measured economic disparity affects educational attainment in hypothetical countries. This study uses a linear regression model to examine how economic inequality affects social outcomes. A statistically substantial positive correlation exists between the Gini coefficient and educational attainment discrepancy. Educational attainment disparity increases by 2.5 years per unit rise in the Gini coefficient, according to the calculated coefficient. This supports the idea that economic inequality increases education gaps, prolonging cycles of disadvantage for vulnerable populations. The study underlines the intricacy of these processes by conceding that regression analysis cannot prove causation. Economic inequality affects educational attainment disparity through policy frameworks, institutional structures, and cultural norms. This highlights the necessity for extensive policy responses to address these issues. The policy ramifications of this study are significant. The findings emphasize the need for fair access to quality education, especially for disadvantaged communities. Targeted actions are needed to reduce economic inequality's impact on education and promote inclusivity. This study examined educational attainment, but its approach and findings are important. The association between economic inequality and social differences is multifaceted, begging for further study. This study adds to the debate between economic inequality and social inequality. This study emphasizes the need for educated and context-sensitive strategies to reduce gaps, enhance social mobility, and create more equitable society as societies face inequality.